Drug Coated Balloons for Dysfunctional Haemodialysis Venous Access: A Patient Level Meta-Analysis of Randomised Controlled Trials. (October 2021) - Fong, Khi Yung; Zhao, Joseph J.; Tan, Eelin; Syn, Nicholas L.; Sultana, Rehena; Zhuang, Kun Da; Chua, Jasmine Ming Er; Patel, Ankur; Irani, Farah G.; Tay, Kiang Hiong; Tan, Bien Soo; Too, Chow Wei
Abstract : Objective: To perform an individual patient data level meta-analysis of randomised controlled trials comparing drug coated balloon angioplasty (DCB) against conventional percutaneous transluminal angioplasty (PTA) in the treatment of dysfunctional haemodialysis venous access. Methods: A search was conducted from inception to 13 November 2020. Kaplan–Meier curves comparing DCB with PTA by target lesion primary patency (TLPP) and access circuit primary patency (ACPP) were graphically reconstructed to retrieve patient level data. One stage meta-analyses with Cox models with random effects shared frailties were conducted to determine hazard ratios (HRs). Dynamic restricted mean survival times (RMST) were conducted in view of violation of the proportional hazards assumption. Conventional two stage meta-analyses and network meta-analyses under random effects Frequentist models were conducted to determine overall and comparative outcomes of paclitaxel concentrations used. Where outliers were consistently detected through outlier and influence analyses, sensitivity analyses excluding those studies were conducted. Results: Among 10 RCTs (1 207 patients), HRs across all models favoured DCB (one stage shared frailty HR 0.62, 95% CI 0.53 – 0.73, p < .001; two stage random effects HR 0.60, 95% CI 0.42 – 0.86, p  = .018, I 2  = 65%) for TLPP. Evidence of time varying effects ( p  = .005) was found. TLPP RMST was + 3.54 months (25.0%) longer in DCB treated patients compared with PTA ( p  = .001) at three years. TLPP at six months, one year, and two years was 75.3% vs. 58.1%, 51.1% vs. 37.1%, and 31.4% vs. 26.0% for DCB and PTA, respectively. The P-Scores within the Frequentist network meta-analysis suggest that higher concentrations of paclitaxel were associated with better TLPP and ACPP. Among six RCTs (854 patients), the one stage model favoured DCB (shared frailty HR 0.72, 95% CI 0.60 – 0.87, p < .001) for ACPP. Conversely, the two stage random effects model demonstrated no significant difference (HR 0.76, 95% CI 0.35 – 1.67, p  = .41, I 2  = 81%). Sensitivity analysis excluding outliers significantly favoured DCB (HR 0.61, 95% CI 0.41 – 0.91, p  = .027, I 2  = 62%). Conclusion: Overall evidence suggests that DCB is favoured over PTA in TLPP and ACPP.